THE LOVE THAT FRIGHTENS. CLINICAL-PEDAGOGICAL REFLECTIONS - Grazia Riva, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The experience of love is common to all human beings, of all ages, social classes and geographical origins (Bettetini, 2012; Passerini, 2008). Contemporary society has typically dragged love out of the intimate sphere, partly as a result of technological advances in the mass communication media, especially Internet. The media constantly dwell on the themes of love and sex, honing in on people’s love lives and making gossip about them a global affair, exposing the most intimate details of the love affairs of the famous and not so famous, and shamelessly flaunting nudity.